Profiles of Executive Function Across Children with Distinct Brain Disorders: Traumatic Brain Injury, Stroke, and Brain Tumor. (15th May 2017) - Araujo, Gabriel C.; Antonini, Tanya N.; Anderson, Vicki; Vannatta, Kathryn A.; Salley, Christina G.; Bigler, Erin D.; Taylor, H. Gerry; Gerhardt, Cynthia; Rubin, Kenneth; Dennis, Maureen; Lo, Warren; Mackay, Mark T.; et al.
Abstract: Objectives: This study examined whether children with distinct brain disorders show different profiles of strengths and weaknesses in executive functions, and differ from children without brain disorder.Methods: Participants were children with traumatic brain injury ( N =82; 8–13 years of age), arterial ischemic stroke ( N =36; 6–16 years of age), and brain tumor ( N =74; 9–18 years of age), each with a corresponding matched comparison group consisting of children with orthopedic injury ( N =61), asthma ( N =15), and classmates without medical illness ( N =68), respectively. Shifting, inhibition, and working memory were assessed, respectively, using three Test of Everyday Attention: Children's Version (TEA-Ch) subtests: Creature Counting, Walk-Don't-Walk, and Code Transmission. Comparison groups did not differ in TEA-Ch performance and were merged into a single control group. Profile analysis was used to examine group differences in TEA-Ch subtest scaled scores after controlling for maternal education and age.Results: As a whole, children with brain disorder performed more poorly than controls on measures of executive function. Relative to controls, the three brain injury groups showed significantly different profiles of executive functions. Importantly, post hoc tests revealed that performance on TEA-Ch subtests differed among the brain disorder groups.Conclusions: Results suggest that different childhood brain disorders result in distinct patterns of executive function deficits that differ from children without brain disorder. Implications for clinical practice and future research are discussed. ( JINS, 2017, 23, 529–538)